Photopatternable solid electrolyte for integrable organic electrochemical transistors: operation and hysteresis. Issue 7 (7th January 2022) - Weissbach, Anton; Bongartz, Lukas M.; Cucchi, Matteo; Tseng, Hsin; Leo, Karl; Kleemann, Hans
Abstract : Entirely photopatternable solid organic electrochemical transistors were fabricated and their excellent performance and pronounced hysteretic behavior studied in detail. Abstract : Organic electrochemical transistors (OECTs) have gained increasing attention during the last decade due to their potential for bioelectronic applications, mainly attributed to their mixed conductivity of both electrons and ions as well as their stability in electrolytic environments. Recent advances opened up new areas of applications for OECTs that range from traditional integrated circuits to unconventional brain-inspired devices. This progress is accompanied by comprehensive developments of new polymeric materials for the active channel. Meanwhile, very little effort has been devoted to the design of materials for the electrolyte – a key element for the performance of OECTs. Here, we present a photopatternable solid electrolyte based on the ionic liquid [EMIM][EtSO4 ] in a polymer matrix. This solid electrolyte can be patterned with standard photolithographic techniques down to a resolution of 10 μm, allowing minimal leakage current and the avoidance of device crosstalk, which is essential for integrated circuits. When employed for PEDOT:PSS-based OECTs, we achieve excellent performance with on–off ratios of 10 5, a threshold voltage of 200 mV, and a sub-threshold swing of 61 mV dec −1 . We characterize the solid electrolyte in detail and investigate the stability of OECT operation in ambient and inert atmosphere. Finally, we examine the pronounced hysteresis found in the transfer characteristics of these devices, for which we provide a way of quantification. This method allows revealing that the hysteresis saturates with the gate voltage range and that its extent is controllable through the scan rate, rendering it a highly appealing feature for integrated circuits and neuromorphic devices.